MEDIA ROLE ON IPO SHARE RETURN DURING THE COVID-19 PANDEMIC - Sumunar, Kurnia Indah; Muhammad, Ridho (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The Covid-19 pandemic has had an impact on various sectors, particularly in the financial sector. One of the triggers is the limitation of activities from the community so that it affects business activities which have an impact on the economy. The company's solution in seeking funds is to conduct an Initial Public Offering (IPO). Companies that conduct IPO have a high risk. This is because investors tend to choose to save their funds in savings, invest in gold and foreign currencies during the pandemic. Moreover, the role of the media today is closely related to the investor decisions. The purpose of this study is to analyze the role of the media on the considerations of investors in buying IPO shares and to analyze the requirement of company performance to conduct an IPO. This study uses a sample of 52 companies that conduct IPOs from March 2020 to May 2021. Secondary data collection uses company financial statements obtained through the IDX official website and Thomson Reuters. This study finds that the role of the media has a positive effect on investors' considerations in buying IPO shares and company size, profitability and leverage ratios are required for companies to conduct IPO.